EFFICACY OF CHRONIC CATARRHAL GINGIVITIS COMPREHENSIVE TREATMENT IN CHILDREN WITH CONGENITAL CLEFT PALATE - Ткаченко, П.І.; Білоконь, С.О.; Лохматова, Н.М.; Білоконь, Н.П. (World of Medicine and Biology, 2015)
It has been found the that the efficacy of comprehensive treatment, involved adjunctive therapy with “Dekasan” antiseptic agent, was much higher than the outcomes of conventional approaches, indicated by the best rates of absolute value of the assessment of oral hygiene and periodontal tissues state. Perspective of further research will encompass the search for more effective pharmacological agents to achieve better results as well as implementation of rehabilitation therapy.